Characterizations of a Quality Certified Athletic Trainer - Raab, Scot (The National Athletic Trainers' Association, Inc., 2011)
CONTEXT: Didactic proficiency does not ensure clinical aptitude. Quality athletic health care requires clinical knowledge and affective traits. OBJECTIVE: To develop a grounded theory explaining the constructs of a quality certified athletic trainer (AT). DESIGN: Delphi study. SETTING: Interviews in conference rooms or business offices and by telephone. PATIENTS OR OTHER PARTICIPANTS: Thirteen ATs (men = 8, women = 5) stratified across the largest employment settings (high school, college, clinical) in the 4 largest districts of the National Athletic Trainers' Association (2, 3, 4, 9). DATA COLLECTION AND ANALYSIS: Open-ended interview questions were audio recorded, transcribed, and reviewed before condensing. Two member checks ensured trustworthiness. Open coding reduced text to descriptive adjectives. RESULTS: We grouped adjectives into 5 constructs (care, communication, commitment, integrity, knowledge) and grouped these constructs into 2 higher-order constructs (affective traits, effective traits). CONCLUSIONS: According to participants, ATs who demonstrate the ability to care, show commitment and integrity, value professional knowledge, and communicate effectively with others can be identified as quality ATs. These abilities facilitate the creation of positive relationships. These relationships allow the quality AT to interact with patients and other health care professionals on a knowledgeable basis that ultimately improves health care delivery. Our resulting theory supported the examination of characteristics not traditionally assessed in an athletic training education program. If researchers can show that these characteristics develop ATs into quality ATs (eg, those who work better with others, relate meaningfully with patients, and improve the standard of health care), they must be cultivated in the educational setting.